Oral health perceptions and client satisfaction among homeless adults attending a community‐centred dental clinic. (14th December 2020) - Hawkesford, JL; Lette, H; Saunders, J; Slack‐Smith, L
Abstract: Background: The homeless face significant barriers accessing dental care. Community‐centred dental clinics might provide more accessible care to this group. This descriptive epidemiological study aimed to measure oral health perceptions and client satisfaction among homeless and similarly disadvantaged adults receiving community‐centred dental care. Methods: A sample of 79 clients attending St Patrick's Oral Health Clinic completed Locker's Global Oral Health Item, the Oral Health Impact Profile 14 and the Client Satisfaction Questionnaire 4. Results: High levels of satisfaction with St Patrick's Oral Health Clinic were based on positive staff attitudes, low cost, time effectiveness and staff sensitivity to anxiety. Ideas for improvement included shorter treatment waiting lists, offering additional treatment types and better communication and advertisement of the service. Compared to the general Australian population, participants reported a relatively poor self‐perception of oral health and a high prevalence and severity of oral health impacts. Conclusions: Participants experienced significant personal and social impacts due to their oral conditions. High levels of client satisfaction reflect the value of community‐centred dental care for this group. An understanding of factors influencing satisfaction might be useful for similar services providing oral care to homeless and similarly disadvantaged groups.